2010
DOI: 10.3945/ajcn.2010.30017
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol adipose tissue stores are depleted after burn injury in pediatric patients

Abstract: Background: We previously showed that thermal injury depletes plasma vitamin E in pediatric burn patients; however, plasma changes may reflect immediate alterations in vitamin E nutriture. Adipose tissue a-tocopherol concentrations are generally accepted to reflect long-term vitamin E status. Objective: To test the hypothesis that thermal injury depletes body stores of vitamin E, a-tocopherol concentrations were measured in adipose tissue samples. Design: Pediatric patients (n = 8) were followed up to 1 y afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 36 publications
1
30
0
2
Order By: Relevance
“…Cette stabilite (de l'ordre de plusieurs annees) fait que ce stock est faiblement mobilisable lors de l'arrêt de supplementation. Cependant, il a ete recemment montre que la vitamine E presente dans le tissu adipeux peutêtre tres rapidement (quelques semaines) mobilisable dans des conditions particulieres d'hypermetabolisme, qui apparaît suite a des brûlures severes chez l'enfant (Traber et al, 2010).…”
Section: Absorption Et Metabolisation De La Vitamine Eunclassified
“…Cette stabilite (de l'ordre de plusieurs annees) fait que ce stock est faiblement mobilisable lors de l'arrêt de supplementation. Cependant, il a ete recemment montre que la vitamine E presente dans le tissu adipeux peutêtre tres rapidement (quelques semaines) mobilisable dans des conditions particulieres d'hypermetabolisme, qui apparaît suite a des brûlures severes chez l'enfant (Traber et al, 2010).…”
Section: Absorption Et Metabolisation De La Vitamine Eunclassified
“…The study found decreasing levels of α-tocopherol in 5 of 8 subjects, with an average decrease of α-tocopherol of 6.1 ± 0.6 μmol/g per day and levels as low as 55% of the original concentrations 3 weeks after injury despite consuming vitamin E at or above the RDA. 9 Insufficient α-tocopherol levels were still seen a month after injury. 9 Although decreased triglyceride levels were also seen in the adipose tissues of these patients, vitamin E levels decreased more significantly, likely due to the use by other tissues during a period of high 184 TOPICS IN CLINICAL NUTRITION/APRIL-JUNE 2013 oxidative stress.…”
Section: Vitamin Status and Supplementation In Pediatric Patients Witmentioning
confidence: 97%
“…9 Insufficient α-tocopherol levels were still seen a month after injury. 9 Although decreased triglyceride levels were also seen in the adipose tissues of these patients, vitamin E levels decreased more significantly, likely due to the use by other tissues during a period of high 184 TOPICS IN CLINICAL NUTRITION/APRIL-JUNE 2013 oxidative stress. 9 The authors determined, based on the tissue biopsies, that the average daily loss of adipose cells was approximately 6 nmol/kg and estimated that a 24-kg child with a burn could be losing as much as 5 mg of α-tocopherol per day.…”
Section: Vitamin Status and Supplementation In Pediatric Patients Witmentioning
confidence: 97%
“…By examining the sequential events occurring in IRI, logical interventions are apparent and a combination of techniques is likely to be successful. Aside from the mechanical preconditioning maneuvers which are relatively risk free, the pharmacological strategies worthy of consideration include, among others, sodium nitrite, 6,23 CD47 antibody, 18,22 hydrogen sulfide, 24Y28 Diannexin, 9 poloxamer 188, 15 desferrioxamine, 57 >-tocopherol, 58 and other antioxidants and streptokinase. 46 A combination of mechanical preconditioning, ROS neutralization, NO stimulation, and an antithrombotic would constitute a logical sequence of IRI combating maneuvers.…”
Section: Phase 2avimmediate Reperfusion Phase: Ros Generation Mitochmentioning
confidence: 99%